The Power of Media Message („The invisible hand“ of the media) - Kulevski, Tsvetan (Research Papers, 2014)
The study focuses on one of the most popular but also the most controversial issue in media knowledge: Is there a media power and what are the mechanisms for its operation? Explored the roots of power, seen through the prism of political science and the nature of the media message from the perspective of journalism theory. Used the method of transdisciplinary approach to the demand for total unification field between the two basic categories of political science and media knowledge. It was discovered and analyzed integrative function of two phenomena: power and media message. A comparative analysis with related concepts such as influence, suggestion, cognitive response, producing the intended results, understanding, agreement, etc. The paper presents several examples of journalistic practice that illustrate both the existence of the power of the media message and its unreality and conventionality. Followed major trends in journalistic work in the modern information society.